Mathematical Modeling Learning Design with PISA Framework on Grade X Function - Nety Wahyu Saputri; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (Jurnal Pendidikan Matematika, 2022)
Mathematical Modeling is the cornerstone and central aspect of the PISA framework. However, students still encounter difficulties in dealing with problems related to mathematical modeling. This study aims to produce a learning trajectory of mathematical modeling on functions material using the context of an online taxibike. Mathematical modeling activities on functions material are designed using the mathematical modeling cycle in the PISA framework. The subjects in this study were students of class X Bina Ilmi IT Senior High School Palembang. The research method used is validation studies. The research consisted of three stages, namely the preparation stage, the experimental design stage consisting of two cycles (cycle I: pilot experiment and cycle II: teaching experiment) and the retrospective analysis stage. Data was collected through observation, interviews and written test (students' work on the activity sheet and the results of pre-test and post-test). The results showed that learning activities that have been designed can assist students in solving mathematical modeling problems on functions. It begins with the formulate, employed, interprete/evaluate process. Through these mathematical modeling processes, students have a better understanding of functions and become accustomed to using mathematical modeling processes in solving contextual problems related to function material.